Exploring the Almost Unknown Trochomorpha (Eupulmonata: Trochomorphidae) from Laos, with Description of Three New Species - Inkhavilay, Khamla; Sutcharit, Chirasak; Pholyotha, Arthit (Tropical Natural History, 2023)
Terrestrial malacofauna in Laos is expected to comprise a large number of species because the country has a large variety of suitable habitats for snail colonization and diversification. The genus Trochomorpha, which exhibits a depressed trochiform shell, is a group of Laotian terrestrial snails for which much is still to be discovered. This study was based on historical records and the recent land snail collections obtained from Laos during 2013–2014. Our results uncovered seven species in Laos based on their distinct shell morphological characters. These comprise four nominal species (T. benigna, T. paviei, T. albofilosa, and T. thachi) and three new species (T. buotia sp. nov., T. speirofascia sp. nov., and T. somsakpanhai sp. nov.). Additionally, the geographic distribution of Trochomorpha species in Laos, except T. benigna, and photos of type specimens of the Indochinese Trochomorpha species are provided.